The effect of like-charge attraction on aerosol growth in the atmosphere of Titan - Lindgren, Eric B.; Stamm, Benjamin; Chan, Ho-Kei; Maday, Yvon; Stace, Anthony J.; Besley, Elena (Elsevier, 2016)
The formation of aerosols in the atmosphere of Titan is based extensively onion-neutral chemistry and physical condensation processes. Herein it is shown that the formation of aerosols may also occur through an alternative pathway that involves the physical aggregation of negatively charged particles, which are known to be abundant in the satellite's atmosphere. It is shown that, given the right circumstances, like-charged particles with a dielectric constant characteristic of nitrated hydrocarbons have sufficient kinetic energy to overcome any repulsive electrostatic barrier that separates them and can subsequently experience an attractive interaction at very short separation. Aerosol growth can then unfold through a charge scavenging process, whereby nitrated aggregates preferentially grow by assimilating smaller like-charged particles. Since hydrocarbon aerosols have much lower dielectric constants, it is shown that a similar mechanism involving hydrocarbon particles will not be as efficient. As a consequence of this proposed growth mechanism, it is suggested that the lower atmosphere of Titan will be enriched in nitrogen-containing aerosols.